Impact of Warm Rolling Process Parameters on Crystallographic Textures, Microstructure and Mechanical Properties of Low-Carbon Boron-Bearing Steels - Mandana Zebarjadi Sar; Silvia Barella; Andrea Gruttadauria; Davide Mombelli; Carlo Mapelli (Metals, 2018)
The effect of the warm rolling process on the microstructure and the mechanical properties of low-carbon high-boron steels are studied in this work. To investigate these effects, boron-bearing low-carbon steel, subjected to roll at three different temperatures, was studied symmetrically and asymmetrically. The results of the experimental trials achieved by mechanical and microstructural analysis revealed that the use of warm rolling can represent a favorable method to suppress strain aging completely, and to eliminate the fluting effect and yield point elongation. In addition, the tensile and elongation properties are modified with the formation of boron nitride precipitates and dislocations in different thermomechanical conditions.